Improving Nutrition through Multisectoral Approaches - World Bank (Washington, DC, 2014)
Nutrition sensitive agriculture aims to maximize the impact of nutrition outcomes for the poor, while minimizing the unintended negative nutritional consequences of agricultural interventions and policies on the poor, especially women and young children. It is agriculture with a nutrition lens, and should not detract from the sector's own goals. The agriculture sector is best placed to influence food production and the consumption of nutritious foods necessary for healthy and active lives. Agricultural productivity, focused primarily on staple grains, does not necessarily reduce under nutrition. Policies that strongly favor staple grains over other crops or foods may skew the balance from nutritious foods.